Gadolinium neutron capture therapy: Calculation of 157Gd kerma factor and a dosimetry study using MCNP Monte Carlo code. (August 2022) - Golshani, Masud; Mowlavi, Ali Asghar; Azadegan, Behnam
Abstract: In this paper, computational dosimetry studies for gadolinium-157 neutron capture therapy ( 157 GdNCT) were carried out using MCNP Monte Carlo code, and the total equivalent dose rate was calculated in a Snyder head phantom with convenient and more accurate methods compared to the previous methods. The potential effectiveness of such therapy was assessed by calculating the therapeutic ratio based on the calculated dose distribution. The total neutron kerma factor for 157 Gd was calculated according to the latest nuclear data. The 157 Gd dose was calculated by kerma approximation and also directly by 157 Gd capture reactions. The kerma of 157 Gd photons was calculated in tumor and compared with the photon dose calculated from the transport of the produced electrons. The results reveal that, due to the severe neutron flux depression and high photon production in the tumor, the kerma approximation does not properly estimate the 157 Gd dose and dose of 157 Gd photons in a small-size tumor. Increasing the size of the tumor, the 157 Gd kerma without considering neutron flux depression and photon kerma approach the dose of 157 Gd and photons, respectively. If 157 Gd is incorporated into the nucleus of the cancer cells, the therapeutic ratio of 157 GdNCT will be greater than one and 157 Gd might, therefore, be a good candidate for neutron capture therapy. Highlights: Computational dosimetry studies for 157 GdNCT using MCNP Monte Carlo code. Calculation of neutron kerma factor for 157 Gd. Kerma approximation can be used for dose of photons and 157 Gd in large-size tumors but not for small-size tumors. The 157 Gd equivalent dose due to internal conversion and Auger electrons is comparable with dose of photons in tumor. The therapeutic ratio of such therapy is reasonable for tumor treatment.